Reconsidering harvested forests for conservation of tree-dwelling bats. - RUSSO, DANILO; GARONNA, ANTONIO PIETRO; CISTRONE L.; JONES G. (Biodiversity and Conservation, 2010)
Intensively managed forests are often seen as of low priority to preserve forest bats. The main conservation strategy recommended, i.e. saving unmanaged ‘‘habitat islands’’ from logging to preserve some suitable habitat, detracts conservationists’ attention from ameliorating conditions for bats in harvested sites. We studied the threatened bat Barbastella barbastellus, mostly roosting in snags, in two beech forests: an unmanaged forest—the main maternity site—and a nearby, periodically logged area. We compared roost availability, roost use, capture rates, food availability and movement between these areas. The managed forest had a greater canopy closure, fewer dead trees, a smaller tree diameter and trees bearing fewer cavities than the unmanaged one. These differences helped explain the larger number of bats recorded in the unmanaged forest, where the sex ratio was skewed towards females. Prey availability was similar in both areas. We radiotracked bats to 49 day roosts. Five individuals caught in the managed area roosted in the unmanaged one at 6.7–8.2 km from the capture site. Few bats roosted in the managed forest, but those doing so proved flexible, using live trees and even rock crevices. Therefore, bats utilise areas in the matrix surrounding optimal roosting sites and sometimes roost there, highlighting the conservation potential of harvested forests. Besides leaving unmanaged patches, at least small numbers of dead trees should be retained in logged areas to favour population expansion and landscape connectivity. Our findings also question the validity of adopting presence records as indicators of forest quality on a site scale.